Effects of an injectable functionalized self-assembling nanopeptide hydrogel on angiogenesis and neurogenesis for regeneration of the central nervous system. Issue 42 (19th October 2017) - Wang, Tzu-Wei; Chang, Kai-Chieh; Chen, Liang-Hsin; Liao, Shih-Yung; Yeh, Chia-Wei; Chuang, Yung-Jen
Abstract : Functionalised self-assembling nanopeptide hydrogel mediates angiogenesis and neurogenesis for injured brain tissue regeneration. Abstract : Brain injury is a devastating medical condition and represents a major health problem. Tissue and organ reconstruction have been regarded as promising therapeutic strategies. Here, we propose a regenerative methodology focusing on the provision of functionalized nanopeptide scaffolds to facilitate angiogenesis and neurogenesis at the brain injury site. The peptide RADA16-SVVYGLR undergoes self-assembly to construct an interconnected network with intertwining nanofibers, and can be controlled to display various physicochemical properties by the adjustment of microenvironmental factors such as pH and ion concentration. Such scaffolds can support endothelial cells to form tube-like structures and neural stem cells to survive and proliferate. In an in vivo zebrafish brain injury model, sprouting angiogenesis and developmental neurogenesis were achieved, and functional recovery of the severed optic tectum was enhanced in RADA16-SVVYGLR hydrogel-implanted zebrafish. This nanopeptide hydrogel was non-toxic to zebrafish embryos during early developmental stages. This angiogenic self-assembling peptide hydrogel had programmable physical properties, good biocompatibility, and regenerative ability for functional recovery in the injured brain. We suggest that functionalized self-assembling peptides encapsulated with neural stem cells or used alone could be an attractive and effective therapeutic modality for brain injury and diseases ( e.g., trauma, stroke, tumor, degenerative neurological disorders, etc. ).